Supportive Work Environments, Innovative Work Behavior, and Job Performance in the Hospitality Industry: Empirical Evidence from Thailand - Chayan Chaiyapruksayanonde; Khwanruedee Ponchaitiwat (Tourism and Hospitality)
The present study aims to examine the effects of physically and psychologically supportive work environments on innovative work behavior and the effects of innovative work behavior on job performance. This study surveyed 275 hotel employees in Thailand, and a rigorous methodology involving path analysis was employed to scrutinize the proposed hypotheses. The study’s findings illuminate the substantial revelation that supportive work environments and innovative work behavior positively and directly impact the cultivation of job performance. Moreover, physically and psychologically supportive work environments positively and indirectly impact the cultivation of job performance. Additionally, this study thoroughly analyzes the implications for management practices, emphasizing the crucial significance of innovative work behavior in shaping job performance outcomes. Furthermore, it provides actionable recommendations for improving physically supportive work environments, empowering psychologically supportive work environments, and creating healthy, innovative work behavior to support cultivating job performance in Thailand’s hospitality industry.